Littérature grecque au Québec - Nécessité de la poésie - Bouchard, Jacques (Études helléniques / Hellenic Studies, 2005)
No serious study has ever been produced on Greek literature in Canada. In fact, very little has been written on the topic, so Jacques Bouchard and Stephanos Constantinides use the following articles ro give an overview, or an initial inventory, which might prove useful in more focussed, more advanced research. There is a sense of urgency here as these authors and their work in Greek may well be forgotten if not studied. Hopefully the second generation of Greek writers who express themselves in English and French will be studied and will find a niche within Canadian and Québécois literature.